Enggagement Twitter DJP: Apa saja yang memengaruhinya? - Padhilah Dikri; Masruri Muchtar; Pardomuan Robinson Sihombing (Directorate General of Taxes, 2024)
Indonesia ranks 10th globally in daily social media usage, with Twitter being a prominent platform due to its tweet character limit, catering to modern individuals with low attention spans. As the Directorate General of Taxes exemplifies, government institutions utilize Twitter's popularity for dissemination through the official account @DitjenPajakRI, which has garnered substantial popularity and engagement. This research analyzes the factors influencing engagement, considering independent variables such as the number of characters, hashtags, mentions, media usage, and the choice of days. This research employs a quantitative descriptive method, employing multiple linear regression analysis on cross-sectional data from the @DitjenPajakRI Twitter account. The study reveals that the number of characters, hashtags, and Saturday tweets significantly and positively influence engagement, while mentions and media attachments exert a negative and significant impact. Tweets on other weekdays show no significant influence. These findings underscore the significance of tweet composition in influencing engagement, providing valuable insights for shaping communication strategies within the Directorate General of Taxes.